Teaching and Assessing Analytical Thinking - Puncochar, Judith (JOMANTARA, 2025)
The focus of this paper is on the pivotal role of analytical thinking in student education, irrespective of the curriculum. Teaching analytical thinking is a vital instructional skill and a foundation of student learning. Instructors should be well-versed in teaching analytical thinking, as it forms the bedrock of critical thinking and problem-solving. Despite not being explicitly listed as one of the seven high-impact teaching practices in undergraduate education by Chickering & Gamson (1987), critical thinking and analytical thinking are frequently cited as Student Learning Outcomes in academic courses and programs in the United States (Grandinetti & Puncochar, 2019; Peñaloza & Puncochar, 2019; Puncochar, Barch, Albrecht, & Klett, 2018). University instructors often claim that they incorporate critical thinking into their teaching to improve student learning outcomes (Janssen et al., 2019). In 2014, Oceans of Data outlined the specific skills and knowledge required to compete in a big-data-centered economy. Analytical thinking ranked highest in both knowledge AND skills. The results were validated by nearly 100 data analyst peers (see Krumhansl, 2016). Although analytical thinking ranked higher than critical thinking in both knowledge and skills, this paper posits that analytical thinking is a necessary precursor to critical thinking and problem-solving.